Building a game with Unity and Blender : learn how to build a complete 3D game using the industry-leading Unity game development engine and Blender, the graphics software that gives life to your ideas /: learn how to build a complete 3D game using the industry-leading Unity game development engine and Blender, the graphics software that gives life to your ideas. (2015) - Eng, Lee Zhi
No abstract available